Analisis Penegakan Hukum terhadap Kasus Ujaran Kebencian di Media Sosial Berdasarkan Hukum Positif di Indonesia - Anisyah Citra; Dwi Novitasari; Syarifah Jamilah; Rosiana Puspita Sari (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The legal meaning of hate speech is that it is prohibited to be spoken, performed, written or acted out because it can cause violence and prejudice against the perpetrator or victim of this behavior. Websites that use or implement hate speech are called hate websites. The research approach method in this legal research is a normative legal approach, namely an approach that uses a legal positivist conception. The normative legal approach in this research means that analyzing problems is carried out using secondary data. This research resulted that in handling hate speech crimes the police enforce the law against hate speech based on the Circular Letter of the Chief of Police Number: SE/06/X/2015 concerning Handling hate speech. Handling hate speech in Indonesia has been supported by the ITE Law, where this law provides more specific regulations regarding criminal acts committed via electronic media.